Etiology and Prognosis of Pneumonia in Patients with Solid Tumors: A Prospective Cohort of Hospitalized Cases. (11th February 2020) - Fernández‐Cruz, Ana; Ortega, Laura; García, Gonzalo; Gallego, Iria; Álvarez‐Uría, Ana; Chamorro‐de‐Vega, Esther; García‐López, José Javier; González‐del‐Val, Ricardo; Martín‐Rabadán, Pablo; Rodríguez, Carmen; Pedro‐Botet, María Luisa; Martín, Miguel; et al.
Abstract: Background: Data on the incidence, etiology, and prognosis of non–ventilator‐associated pneumonia in hospitalized patients with solid tumors are scarce. We aimed to study the characteristics of non–ventilator‐associated pneumonia in hospitalized patients with solid tumors. Materials and Methods: This was a prospective noninterventional cohort study of pneumonia in patients hospitalized in an oncology ward in a tertiary teaching hospital. Pneumonia was defined according to the American Thoracic Society criteria. Patients were followed for 1 month after diagnosis or until discharge. Survivors were compared with nonsurvivors. Results: A total of 132 episodes of pneumonia were diagnosed over 1 year (9.8% of admissions to the oncology ward). They were health care–related (67.4%) or hospital‐acquired pneumonia (31.8%). Lung cancer was the most common malignancy. An etiology was established in 48/132 episodes (36.4%). Knowing the etiology led to changes in antimicrobial therapy in 58.3%. Subsequent intensive care unit admission was required in 10.6% and was linked to inappropriate empirical therapy. Ten‐day mortality was 24.2% and was significantly associated with hypoxia (odds ratio [OR], 2.1). Thirty‐day mortality was 46.2%. The independent risk factors for 30‐day mortality were hypoxia (OR, 3.3), hospital acquisition (OR, 3.1), and a performance status >1 (OR, 2.6). Only 40% of patients who died within 30 days were terminally ill. Conclusion: Pneumonia is a highly prevalent condition in hospitalized patients with solid tumors, even with nonterminal disease. Etiology is diverse, and poor outcome is linked to inappropriate empirical therapy. Efforts to get the empirical therapy right and reach an etiological diagnosis to subsequently de‐escalate are warranted. Implications for Practice: The present study shows that pneumonia is a prevalent infectious complication in patients admitted to oncology wards, with a very high mortality, even in non–terminally ill patients. Etiology is diverse, and etiological diagnosis is reached in fewer than 40% of cases in nonintubated patients. Intensive care unit admission, a marker of poor outcome, is associated with inappropriate empirical therapy. These results suggest that, to improve prognosis, a more precise and appropriate antimicrobial empirical therapy for pneumonia in patients with solid tumors is necessary, together with an effort to reach an etiological diagnosis to facilitate subsequent de‐escalation. Abstract : Pneumonia is a complication in patients admitted to oncology wards, but data on incidence, etiology, and prognosis is lacking. This articles reports on characteristics of nonventilator‐associated pneumonia in hospitalized patients with solid tumors.